1996
DOI: 10.1126/science.271.5245.64
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mutant CFTR in Hypersusceptibility of Cystic Fibrosis Patients to Lung Infections

Abstract: Cystic fibrosis (CF) patients are hypersusceptible to chronic Pseudomonas aeruginosa lung infections. Cultured human airway epithelial cells expressing the ΔF508 allele of the cystic fibrosis transmembrane conductance regulator (CFTR) were defective in uptake of P. aeruginosa compared with cells expressing the wild-type allele. Pseudomonas aeruginosa lipopolysaccharide (LPS)-core oligosaccharide was identified as the bacterial ligand for epithelial cell ingestion; exogenous oligosaccharide inhibited bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
295
4
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 399 publications
(320 citation statements)
references
References 29 publications
13
295
4
8
Order By: Relevance
“…In transgenic CFTR-knockout mice, NF-κB nuclear translocation occurs much later in the airway epithelial cells [28], probably contributing more to the harmful inflammation that ensues in this environment instead of the protective inflammation that occurs when functional CFTR is present. Overall, this scenario wherein WT-CFTR binding of P. aeruginosa leads to protection and failure of this interaction in CF leads to infection is supported by data obtained in numerous in vitro and, importantly, in υivo, studies demonstrating CFTR-dependent responses to P. aeruginosa in a variety of lung epithelial cell lines and in transgenic animals [8][9][10][11][12][27][28][29]31,36]. Thus, it seems that CFTR facilitates bacterial clearance and modulates innate immunity towards P. aeruginosa in lung epithelial cells by being the linchpin needed for coordinating multiple host responses involved in resisting infection and maintaining tissue homeostasis in the long run.…”
Section: Host Factors Allowing P Aeruginosa To Initiate Infection Inmentioning
confidence: 75%
See 3 more Smart Citations
“…In transgenic CFTR-knockout mice, NF-κB nuclear translocation occurs much later in the airway epithelial cells [28], probably contributing more to the harmful inflammation that ensues in this environment instead of the protective inflammation that occurs when functional CFTR is present. Overall, this scenario wherein WT-CFTR binding of P. aeruginosa leads to protection and failure of this interaction in CF leads to infection is supported by data obtained in numerous in vitro and, importantly, in υivo, studies demonstrating CFTR-dependent responses to P. aeruginosa in a variety of lung epithelial cell lines and in transgenic animals [8][9][10][11][12][27][28][29]31,36]. Thus, it seems that CFTR facilitates bacterial clearance and modulates innate immunity towards P. aeruginosa in lung epithelial cells by being the linchpin needed for coordinating multiple host responses involved in resisting infection and maintaining tissue homeostasis in the long run.…”
Section: Host Factors Allowing P Aeruginosa To Initiate Infection Inmentioning
confidence: 75%
“…To wit, results showing that WT-CFTR is a receptor for P. aeruginosa that mediates effective innate immunity and that this receptor is not functional in CF [9,10] are the ones most consistent with clinical and experimental observations. One curious additional observation about this interaction has also been reported: the mucoid strains of P. aeruginosa responsible for chronic infection lose the bacterial ligand for CFTR [8,11,12], indicating that the P. aeruginosa-CFTR direct interaction is likely to be primarily of relevance to the early stages of infection, whereas in the later stages of infection other properties of the bacterium and the CF host conspire to allow for maintenance of the chronic infectious state.…”
Section: Histopathologic Basis For Defining Relevant Interactions Betmentioning
confidence: 97%
See 2 more Smart Citations
“…demonstrated a defect of the innate immune function of epithelial cells in the respiratory tract of cystic fibrosis mice. They showed that the lipopolysaccharide (LPS)-molecule of P. aeruginosa binds to a short amino acid sequence in CFTR (AA 103-117) [13]. This interaction mediates internalisation of P. aeruginosa into lung epithelial cells.…”
Section: Inflammation In Cystic Fibrosismentioning
confidence: 99%